2013
DOI: 10.1371/journal.pone.0063542
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen Induced Products of Linoleates, 10- and 12-(Z,E)-Hydroxyoctadecadienoic Acids (HODE), Can Be Potential Biomarkers for Early Detection of Type 2 Diabetes

Abstract: Current diagnostic tests such as glycemic indicators have limitations for early detection of impaired glucose tolerance (IGT), which leads to diabetes. Oxidative stress induced by various oxidants in a random and destructive manner is considered to play an important role in the pathophysiology of a number of human disorders and diseases such as impaired glucose tolerance. We have developed an improved method for the measurement of in vivo lipid peroxidation, where the presence of 8-iso-prostaglandin F2α (8-iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 43 publications
0
64
0
2
Order By: Relevance
“…Our measurement revealed that HODE isomers can be prominent biomarkers for some diseases [4][5][6][7]. For example, plasma levels of 10-and 12-(Z,E)-HODEs, which are singlet oxygen-specific products, are significantly correlated with glucose levels in patients with early-stage type 2 diabetes [6,7].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our measurement revealed that HODE isomers can be prominent biomarkers for some diseases [4][5][6][7]. For example, plasma levels of 10-and 12-(Z,E)-HODEs, which are singlet oxygen-specific products, are significantly correlated with glucose levels in patients with early-stage type 2 diabetes [6,7].…”
Section: Introductionmentioning
confidence: 81%
“…As HODEs, the reduced forms of HPODEs, are stable under physiological conditions, we developed a method to measure HODE isomers in the same sample, including 9-(Z,E) and 9-(E,E)-HODE, 10-(Z,E)-HODE, 12-(Z,E)-HODE, and 13-(Z,E) and 13-(E,E)-HODE, to understand the oxidation mechanism in vivo [2,3]. Our measurement revealed that HODE isomers can be prominent biomarkers for some diseases [4][5][6][7]. For example, plasma levels of 10-and 12-(Z,E)-HODEs, which are singlet oxygen-specific products, are significantly correlated with glucose levels in patients with early-stage type 2 diabetes [6,7].…”
Section: Introductionmentioning
confidence: 86%
“…4 . Recently, we found that singlet oxygen-specific products 10-and 12-HODEs are promising biomarkers for the early detection of diabetes 27 , which is discussed in more detail later. Furthermore, we have demonstrated that sublethal concentrations of racemic 10-and 12-HODEs exert cytoprotective effects in vitro.…”
Section: Hodesmentioning
confidence: 94%
“…Strikingly, 10-and 12-HODE levels in the plasma of healthy volunteers Normal were similar, suggesting that singlet oxygen attacks 10-and 12-positions of linoleates equally Table 1, unpublished data calculated from ref. 27 . It is interesting to note that 10-HODE levels tended to increase with decreasing glucose tolerance, more noticeable than 12-HODE although not significant.…”
Section: Hodesmentioning
confidence: 99%
“…(52,53) Briefly, after an extraction with chloroform and ethyl acetate, t8-iso-PGF 2α , t-HETE, and t-HODE in plasma and RBCs were analyzed by LC-MS/MS. LC was carried out on an ODS column in a column oven set at 30°C.…”
Section: Methodsmentioning
confidence: 99%